THE ROLE OF HYPERBOLE IN ENGLISH LITERATURE - Kazakbaeva , Aziza (Educational Research in Universal Sciences, 2024)
This article explores the significance of hyperbole in English literature. Hyperbole, as a rhetorical device, has been used extensively by writers to create emphasis, evoke emotions, and add depth to their works. The article delves into the historical origins of hyperbole, its various forms and functions, and its impact on the readers’ interpretation of literary texts. The study also examines specific examples of hyperbole in famous literary works to illustrate its effectiveness in conveying exaggerated or heightened expressions. Furthermore, the article discusses the implications of hyperbole in shaping the readers’ understanding and appreciation of literature.